PERIBAHASA MASYARAKAT DAYAK KEBAHAN PENYELOPAT DESA ENGKURAI KECAMATAN PINOH UTARA KABUPATEN MELAWI - Christy, Piska Sarry Kurnia; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The study of the Dayak Kebahan Penyelopat proverbs was carried out based on the existence of proverbs in the Dayak Kebahan Pelopat community which are currently rarely used. Proverb research aims to inventory, classify the types, forms, functions and meanings of Dayak Kebahan Penyelopat proverbs using semantic studies. The method used in this research is a descriptive method in the form of qualitative research. This research uses observation, interview, recording and note-taking techniques, and documentation study. The sources of data in this study are the traditional temanggung and the Dayak Kebahan Penyelopat community. The study managed to inventory 68 proverbs. These proverbs are grouped by type, namely proverbs, parables, expressions, imagery, teromba, pendita's tongue, and simile. The most prominent type of Dayak Kebahan Penyelopat proverb is the proverb. The types of proverbs of Dayak Kebahan Penyelopat in this study are classified based on the types of proverbs, namely 29 types of proverbs, 12 types of parables, 14 types of expressions, 6 types of imagery, 2 types of teromba, 4 types of pendita's tongue, and 1 type of simile. The function of the Dayak Kebahan Penyelopat proverb in this study is classified based on the function of proverbs as advice totaling 27, the function of proverbs as satire amounting to 35, the function of proverbs as compliments amounting to 4, the function of proverbs as a diplomatic language amounting to 1, and the function of proverbs as customary law 1.